Penerapan Model Kooperatif Tipe Make A Match Dalam Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran Ilmu Pengetahuan Alam - Aswan, Niki; Amal, Amri; aseh, Muji (Universitas Negeri Makassar, 2024)
This research is a Classroom Action Research (PTK) conducted at SDN 105 Lamasi which aims to improve student learning outcomes in natural science subjects by using a make a match type cooperative learning model at SDN 105 Lamasi. The design in this study uses a design developed by Kemmis and Mc Taggart which consists of four stages, namely the planning, implementation, observation and reflection stages. The subjects of the study were class IV students totaling 20 students. Data collection techniques are carried out by observation and tests. The research instrument uses observation sheets and fill-in-the-blank questions, the collected data is analyzed quantitatively and qualitatively. The results showed that the indicators of the implementation of learning from cycle I amounted to 77.5%, increased in cycle II by 92.5% and entered the very good category. Student learning activities in the first cycle amounted to 63.63%, increased in the second cycle by 91% and entered the very active category. Student learning test results in cycle I by 60%, increased in cycle II by 80%. The learning outcomes of grade IV students of SDN 105 Lamasi have succeeded in improving student learning outcomes in Natural Science subjects by using the make a match type cooperative model. If confirmed with the school's KKM score in science subjects, students are declared successful if they reach 70% who get a score of 70 and above. These results show that the application of the make a match type cooperative model can improve science learning outcomes of grade IV students of SDN 105 Lamasi in cycle II.